"Overcrowding the Profession" – an Artificial Argument? - Eyal Katvan (Oñati Socio-Legal Series)
It has been claimed that Israel has the highest per capital rate of lawyers in the world, resulting in belief that the Israel Bar is overpopulated. The first law colleges, which were established 20 years ago, are newcomers to the production of legal professions. The leadership of the Israel Bar have held the law colleges responsible for Israel’s overpopulation of lawyers and for the legal profession’s decline in prestige. This paper examines whether the perception of overcrowding of the profession is a new “discovery” or rather the recycling of a standard dynamic between professionals and legal education institutions. While this paper focuses specifically on Israel, concern about the overpopulation of the profession has become a central concern in many other jurisdictions.